Preparation of graphene oxides functionalized with ferrocene for the thermal decomposition of ammonium perchlorate - Liu, Jinyi; Yu, Haojie; Wang, Li; Vatsadze, Sergey Z.; Chen, Dingning; Wu, Xudong; Gong, Xiaodan; Wang, Yu (Molecular catalysis, 2023)
•Four GOs functionalized with FC as burning rate catalysts were prepared.•The catalytic effect, combustion performance and anti-migration ability of burning rate catalysts were investigated.•The possible catalytic mechanism and anti-migration mechanism of burning rate catalysts were studied in detail.•The pyrolysis temperature of ammonium perchlorate and the combustion pressure index of burning rate catalysts were decreased. Moreover, the burning rate and the anti-migration performance of burning rate catalysts were improved significantly. Ferrocene (Fc)-based compounds as the burning rate catalysts (BRCs) for the thermal decomposition of ammonium perchlorate (AP), a vital oxidizer in composite solid propellants (CSPs), were received extensive attention due to its excellent catalytic effect. However, most of them are easy to migrate and the in situ produced metal oxide nanoparticles at high temperature tend to agglomerate, affecting the catalytic efficiency. Herein, a series of GOs functionalized with Fc were fabricated and studied as BRCs in this work. The results showed that these compounds can accelerate AP decomposition and enhance the combustion performance of CSPs, which was ascribed to the good thermal conductivity, electrical conductivity, larger steric hindrance and specific surface area. Among them, GOCu-AMTZ-Fc showed the best catalytic performance. The pyrolysis temperature of AP was reduced from 420.9 °C to 337.6 °C. Meanwhile, the burning rate of propellant was increased from 1.64 mm/s to 2.20 mm/s and the related pressure index was decreased by nearly half. Moreover, their anti-migration ability was improved greatly. The work indicated that GOs functionalized with Fc have a potential application as BRCs in CSPs. [Display omitted]